Osteosarcoma-on-a-chip: a physiologically relevant human-based microfluidic platform for drug screening - Monteiro, Cátia Filipa Rodrigues (2024)
The lack of predictability of the current pre-clinical models is a major concern in cancer research. Neglecting the tridimensionality of native tissues and the importance of the mechanical stimuli provided by fluid flow inside the human body hamper the faithful recapitulation of several physiopathological mechanisms involved in tissue homeostasis and cancer. The present thesis proposes the development of humanized 3D static and dynamic osteosarcoma (OS) tumor models by exploring the feasibility of human methacryloyl platelet lysate (PLMA) biomaterial to support the study of distinct stages of tumor progression. The main goals of the developed 3D models were: (i) validate PLMA hydrogels for tumor invasion; (ii) study the influence of stromal cells in tumor invasive behavior; (iii) develop a new strategy for generating 3D spheroid-like cell-rich assemblies; and (iv) engineer a microfluidic tumor-on-a-chip model to assess the metastatic tumor inter-heterogeneity. The potential of human-derived PLMA hydrogels to support mesenchymal stem cell and tumor cell spheroid growth and invasion was validated, granting a new 3D platform for the development of more complex tumor models. The co-culture of stromal cells, namely mesenchymal stem cells and osteoblasts, in the tumor spheroid surroundings, enabled a faithful mimicry of the synergistic tumor-stromal cell paracrine signaling crucial for enhanced tumor invasion and stromal cell migration toward the tumor. The tri-culture model also successfully recreated the protective role exerted by stromal cells in tumor resistance against anti-cancer therapies. In an immunomodulatory 3D OS model, the pro-tumoral molecular environment generated by the PLMA-embedded tumor stimulated an anti-inflammatory macrophage phenotype that, in turn, enhanced tumor proliferation and invasiveness. Aiming to propose a new method of generating biomaterial-incorporating cell aggregates, PLMA-based nanofibrils were fabricated and assembled into a supramolecular ultrathin and flexible membrane, which was folded by cells into a 3D PLMA-cell microtissue. Recognizing the pivotal role of fluid flow-induced mechanical stimuli in regulating tumor progression and metastasis, a human tumor-on-a-chip co-culture OS model was microengineered to emulate the distinct metastatic ability inherent to tumors of similar origin tissue. The biologically-relevant cell-cell and cell-matrix interaction prompted an accurate recreation of the metastatic tumor inter-heterogeneity and respective biomarker profile, while emphasizing the importance of fluid dynamics. Overall, these studies highlight the PLMA as a promising human-derived biomaterial to pursue mechanistic studies on early tumor metastatic events, paving the way toward the next generation of humanized organ-on-a-chip devices.